Pengaruh Orientasi Kewirausahaan dan Strategi Bisnis terhadap Peningkatan Kinerja Wirausaha Kosmetik di Wuluhan Jember - Putri, Elsa Catrika; Hermawan, Haris; Rusdiyanto, Rusdiyanto (BUDGETING : Journal of Business, Management and Accounting, 2024)
This study entitled "The Influence of Entrepreneurial Orientation Models and Business Strategy on Increasing the Performance Cosmetic Entrepreneurs in Wuluhan Jember" which aims to determine the partial effect of entrepreneurial orientation models and business strategies on entrepreneurial performance. This research uses descriptive quantitative research with a population of all female cosmetics entrepreneurs in Wuluhan and a sample of this study amounting to 46 respondents. Data collection methods used were interviews, observations and questionnaires and were analyzed using regression analysis and t-test with the help of the SPSS 26 application. The results of this study indicate that the entrepreneurial orientation model has a partial effect on entrepreneurial performance by 0.362. Meanwhile, business strategy has a partial effect on entrepreneurial performance by 0.375. Keywords: Business Strategy, Entrepreneurial Performance, Entrepreneurial Orientation Model,